Popular Religions and Multiple Modernities: A Framework for Understanding Current Religious Transformations - Parker-Gumucio, C (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Popular, ethnic, and folk religions endure in all regions of the planet, but specially in underdeveloped or developing non-Western countries. The main objective of this paper was to propose a framework for understanding this popular religious trend. Although religion in general has previously been linked to multiple modernities, the revitalization of popular religions has not. While Eisenstadt’s original theory of multiple modernities has been criticized on several aspects, his interpretative approach is valid provided that the contradictory dynamics of modernizing processes are recognized. The epistemological shift suggested by this article involves recognizing the biases that Western sociology has brought to its analysis of religions. Once we treat modernities as multiple, the specificity of each modernity opens up the spectrum of religious alternatives that flourish in every geo-cultural area. The growing diversity of popular religious expressions in the Global South stems from the fact that they are supported by thousands of believers. Their lived religions spills beyond religious institutions. These popular religiosities are the main sources of religious diversities and religious resistance in the context of multiple modernities. Lived religion and symbolic action allow us a better understanding of the magical-religious expressions of peoples of the world. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.